Ergonomic Redesign Model to reduce musculoskeletal disorders in a cluster of SMEs in the clothing accessories sector - Aquino Rojas, Daniel Martin (2022)
The Peruvian manufacturing industry is one of high impact in Latin America with excellent quality materials and massive productive quantities making it an important industry for the country itself. Even so, with this sector being so significant, the prevalence rate of musculoskeletal disorders (MSDs) remains high for companies with little capital and no investment capacity, such being the small and medium-sized enterprises (SMEs) of the industry. Either due to mishandling of machinery or repetitiveness of labor, musculoskeletal disorders are a prevalent problem for manufacturing industries with little to no information on ergonomic ways of control as well as having a Lean focus to add value to the process. This paper seeks to find the validity of a model to reduce absenteeism and exposure to musculoskeletal disorders using ergonomic and Lean tools to promote safe practices and the preservation of health in turn with work productivity on SMEs from the clothing accessory sector. This model was able to reduce exposure to MSDs by 67.27% and reduced the company's absenteeism rate by 52.85% getting to considering levels for industry standards and validating the effectiveness of similar models.